Mexiletine in the Treatment of LQT2, LQT3, and Acquired LQTS: A Meta-Analysis - Dhiya Ihsan; Mohammad Iqbal; Charlotte Johanna Cool; Chaerul Achmad; Miftah Pramudyo; Hawani Sasmaya Prameswari; Mohammad Rizki Akbar (Majalah Kardiologi Indonesia)
Background: High mortality in patients with Long QT Syndrome (LQTS) can be reduced with proper treatment. Gene-specific therapy is crucial, as many treatments are not equally effective across different LQTS types. While mexiletine has been established in the treatment of LQT3, its use in other types of LQT need further evaluation.